From Fashion to Electronics: Analyzing Shopee Indonesia Email Marketing Content Across Different Product Categories - Rahayu, Tri Anita; Rahyadi, Irmawan; La Mani, La Mani (UI Scholars Hub, 2025)
This study explores the email marketing content employed by Shopee Indonesia across various product categories, including fashion, health & beauty, electronics, digital products, and home & living. By analyzing the variations in themes, messaging, and promotional tactics, the research aims to understand how Shopee Indonesia customizes its email content to optimize engagement and conversion rates across these diverse categories. The findings reveal that Shopee Indonesia employs distinct content strategies tailored to the specific characteristics and consumer preferences associated with each category, highlighting the platform's strategic approach to targeted marketing.